An innovative hybrid-solar-vacuum dryer to produce high-quality dried fruits and vegetables. (April 2021) - Roratto, Thayla B.; Monteiro, Ricardo L.; Carciofi, Bruno A.M.; Laurindo, João B.
Abstract: Food drying uses much energy and is considered a high carbon footprint process. Solar drying is sustainable, but the dryers must be improved to produce high-quality foods in short times. In this study, a hybrid-solar vacuum dryer was designed, built, and applied to fruit dehydration. A solar heater was coupled to a thermally insulated reservoir with electrical resistances to provide hot water at 90 °C as the indirect heating medium. Drying chambers with a full capacity of 4 kg of sliced food were operated under vacuum or vacuum pulses (conductive multiflash drying). Banana slices could be dried with the most basic equipment configuration (vacuum chamber, vapor condenser, and vacuum pump), resulting in homogeneous and crispy snacks. The dryer was also tested for persimmons and carrots. The drying of all the fruit and vegetable samples resulted in dried and crisp products in 3–4 h, depending on the drying temperature, and the use of continuous electric support for temperatures higher than 70 °C. The hybrid solar dryer operating under vacuum is an innovative and clean technology that results in high-quality products and has excellent potential to be used in small farms. Highlights: A hybrid solar dryer operating under vacuum was designed and tested. The dryer has an even temperature distribution that results in high-quality dried foods. . The dryer can dry 4 kg of fruits or vegetables in 4 h, resulting in crisp snacks. The application of vacuum pulses during drying creates a new microstructure and texture. .